Pembelajaran Terintegrasi Pendidikan Agama Islam Di Smp Islam Terpadu Syakur Al Marzuqi - M. Ali Baidlowi M. Z.; Giyoto Giyoto (Departement of Mathematics Education, 2024)
Learning is a process of interaction between students and educators with learning resources through appropriate strategies, approaches, methods, and learning models in a learning environment to achieve learning objectives, curriculum goals, and educational goals. This research is a qualitative study. The research location is at the Syakur Al-Marzuqi Integrated Islamic Middle School, Ngelingi Hamlet, Bareng Village, Ngasem District, Bojonegoro Regency. This school is under the auspices of an Islamic boarding school, so integration between general and religious studies definitely occurs. As for data collection techniques, they are carried out through observation, interviews, and documentation. Meanwhile, for data analysis, the researcher uses the Miles and Huberman data analysis model, whereby after the data is collected (data collection period), data reduction, data display, and conclusion drawing are performed. The design of this Islamic Religious Education learning includes active learning methods. The steps of learning in this school are broadly divided into 3 stages: initial activities, core/main material activities, and closing activities. (2) In this application, the role of the teacher must be more professional, both in mastering the material and classroom management. The teacher must also be able to control the learning process in the classroom so that students do not become bored with the material and the way the teacher delivers the material. (3) The implications of this learning are effective for student learning outcomes and also impact the Islamic Religious Education subject teachers.